2013
DOI: 10.1063/1.4818554
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution and scaling of mixing in two-dimensional Rayleigh-Taylor turbulence

Abstract: We report a high-resolution numerical study of two-dimensional (2D) miscible Rayleigh-Taylor (RT) incompressible turbulence with the Boussinesq approximation. An ensemble of 100 independent realizations were performed at small Atwood number and unit Prandtl number with a spatial resolution of 2048 × 8193 grid points. Our main focus is on the temporal evolution and the scaling behavior of global quantities and of small-scale turbulence properties. Our results show that the buoyancy force balances the inertial f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 48 publications
3
11
1
Order By: Relevance
“…It is seen clearly that in the range 1.6 t/τ 4 two types of lines collapse roughly on top of each other, indicating a quadratic growth of h(t). Further studies show that the power spectra (not shown here) of both the velocity and temperature files obtained within the self-similar range cover a broad range of scales [40], indicating that a turbulent state has been well developed. Therefore, we shall later analyze the temporal evolution of Q(η) within this time range.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…It is seen clearly that in the range 1.6 t/τ 4 two types of lines collapse roughly on top of each other, indicating a quadratic growth of h(t). Further studies show that the power spectra (not shown here) of both the velocity and temperature files obtained within the self-similar range cover a broad range of scales [40], indicating that a turbulent state has been well developed. Therefore, we shall later analyze the temporal evolution of Q(η) within this time range.…”
Section: Resultsmentioning
confidence: 62%
“…The direct numerical simulations are based on a compact fourth-order finite-difference scheme, proposed by Liu et al [41], and the accuracy, stability, and efficiency of the scheme have been examined in great detail [41,42]. Recently, we have applied the same numerical code to study, respectively, small-scale properties in the 2D RT system [40] and turbulent heat transport in 2D Rayleigh-Bénard convection [43]. In the present study, the number of grid points is set to 4096 × 8193 in all the runs to achieve a sub-Kolmogorov-scale resolution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is straightforward to deduce that V t has an obvious linear relationship with U. Additionally, the physical parameters, including κ, ϕ and ε, have an impact on the V t -U relationship. Furthermore, for a given cylinder, there exists a U i to make V t /(U − U i ) a constant, and this means that the cylinder translation system is selfsimilar (Zhou, 2013). Therefore, the terminal velocity can be estimated by extrapolation of the linear relationship obtained in this simulation.…”
Section: The Cylinder Could Attain Terminal Velocitymentioning
confidence: 99%